Military Integration after Civil Wars : Multiethnic Armies, Identity and Post-Conflict Reconstruction. - Gaub, Florence (Cass Military Studies, 2010)
This book examines the role of multiethnic armies in post-conflict reconstruction, and demonstrates how they can promote peacebuilding efforts. The author challenges the assumption that multiethnic composition leads to weakness of the military, and shows how a multiethnic army is frequently the impetus for peacemaking in multiethnic societies. Three case studies (Nigeria, Lebanon and Bosnia-Herzegovina) determine that rather than external factors, it is the internal structures that make or break the military institution in a socially challenging environment. The book finds that where the polit.